Effects of incorporating different chalcogenophene comonomers into random acceptor terpolymers on the morphology and performance of all-polymer solar cells. Issue 5 (12th January 2018) - An, Yujin; Oh, Jiyeon; Chen, Shanshan; Lee, Byongkyu; Lee, Sang Myeon; Han, Daehee; Yang, Changduk
Abstract : A new family of NDI-based random terpolymers, incorporating a small amount (10%) of different chalcogenophene units (-Fu, -Th, -Se) was synthesized and investigated for all-PSCs. Abstract : A new family of naphthalenediimide (NDI)-bithiophene-based random terpolymers (PNDI-Fu10, PNDI-Th10, and PNDI-Se10) was prepared by incorporating a small amount (10 mol%) of different chalcogenophene units, namely furan (Fu), thiophene (Th), and selenophene (Se), into a poly(( N, N '-bis(2-octyldodecyl)-naphthalene-1, 4, 5, 8-bis(dicarboximide)-2, 6-diyl)- alt -5, 5′-(2, 2′-bithiophene)) (P(NDI2OD-T2)) backbone. The terpolymers all exhibited negligible optical property and frontier energy level differences. Interestingly, the blend film morphology and photovoltaic performance of all-polymer solar cells (all-PSCs), comprising a random terpolymer series as an acceptor and poly(6-fluoro-2, 3-bis-(3-octyloxyphenyl)quinoxaline-5, 8-dyl- alt -thiophene-2, 5-diyl) (FTQ) as a donor, were strongly dependent on the type of chalcogenophene. Consequently, the all-PSCs revealed a clear variation in short-circuit current density ( J SC ) and fill factor (FF) while retaining identical open-circuit voltages ( V OC ). The greatest power-conversion efficiency of 5.88% with a high J SC of 10.77 mA cm −2 was observed for PNDI-Th10:FTQ because of a synergistic contribution from a more preferential π-face-on orientation and suppression of bimolecular/geminate recombination. This was confirmed by a detailed investigation on the morphology and charge dynamic structural properties. In addition to understanding their effects on photovoltaic characteristics, this study demonstrates that introducing a small amount of the chalcogenophenes into a well-performing polymer is a simple and effective method to improve J SC values while maintaining V OC s of the parent polymers.